Mitochondrial NDUFA4L2 protein promotes the vitality of lung cancer cells by repressing oxidative stress. Issue 4 (2nd February 2019) - Meng, Lifei; Yang, Xuhui; Xie, Xiao; Wang, Mingsong
Abstract : Background: Non‐small cell lung cancer (NSCLC) accounts for a significant proportion of cancer‐related deaths and lacks an effective treatment strategy. NSCLC tissues are generally found in a low oxygen environment. The NDUFA4L2 protein, located in the mitochondria, is encoded by the nucleus genome and is considered a crucial mediator that regulates cell survival. A better understanding of the mechanism of NDUFA4L2 in NSCLC survival in hypoxic environments is essential to design new therapeutic methods. Methods: Twenty NSCLC and corresponding paired non‐tumorous lung tissue samples were collected. NSCLC cell lines were cultured in hypoxic conditions to investigate the mechanism of NDUFA4L2 in NSCLC. The role of NDUFA4L2 was confirmed by using Western blotting, reactive oxygen species measurement, flow cytometry, immunofluorescence analysis, and wound healing and colony formation assays. Results: The expression of HIF‐1α and mitochondrial NDUFA4L2 increased in NSCLC cell lines cultured in hypoxic conditions (1% O2 ). NDUFA4L2 was drastically overexpressed in human NSCLC tissues and cell lines cultured in hypoxic conditions. HIF‐1α regulated the expression of NDUFA4L2. Knockdown of NDUFA4L2 notably increased mitochondrial reactive oxygen species production, which suppressed the viability of NSCLC. Conclusion: In conclusion, overexpression of NDUFA4L2 is a key factor for maintaining NSCLC growth, suggesting that mitochondrial NDUFA4L2 may be a potential target for the treatment of lung cancer.